Meningkatkan Kompetensi Guru Pendidikan Agama Kristen melalui Pendekatan Massive Open Online Course (MOOC) di Era Society 5.0 (Sekolah Tinggi Agama Kristen Arastamar Grimenawa J, 2025)
Christian Religious Education requires an increase in teacher competence to face the dynamics of the Society 5.0 era, in which information technology plays a key role. The Massive Open Online Course (MOOC) approach emerges as an innovative solution to support teachers' professional development. This research discusses the methodology of improving the competence of Christian Religious Education teachers through the application of MOOC in the era of Society 5.0. The needs and objectives identification stage was conducted to understand the challenges and needs of teachers in integrating the teachings of Christianity with technological developments. MOOC selection and evaluation became the next focus to ensure quality content and relevance to the context of Christian religious education. Teacher professional development programs are designed and implemented by integrating MOOCs as the main resource. The methodology also incorporated mentoring and continuous evaluation. Involving the library method, this research emphasizes literature search and library resources as supporting the integration of Christianity teachings with the concept of Society 5.0. The results of this study are expected to contribute to practical and theoretical understanding to improve the competence of Christian Religious Education teachers in facing the challenges of the Society 5.0 era.